2007
DOI: 10.3748/wjg.v13.i38.5065
|View full text |Cite
|
Sign up to set email alerts
|

Modifications produced by selective inhibitors of cyclooxygenase and ultra low dose aspirin on platelet activity in portal hypertension

Abstract: INTRODUCTIONPortal hypertension is a major complication of chronic liver disease. In its pathophysiology, increased hepatic resistance is followed by a hyperdynamic circulatory state [1] . This hyperdynamic state, in which nitric oxide (NO) and prosatcyclin (PGI2) are important vasoactive substances, induces a decreased platelet activity, even in the absence of hepatic damage. Although NO plays an important role in modifying platelet adhesion in portal hypertension [2] , PGI2, a powerful vasodilator prostanoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…(7)). This hypothesis is supported by the observation that very low doses of Aspirin can reduce bleeding in portal hypertension patients, which has been explained by COX-2 inhibition [47]. Based on the LeadHopper® prediction, one might speculate that this surprising opposite effect to the standard indication of Aspirin might also be attributed to PTB-1B inhibition: PTP-1B is required for normal platelet thrombus formation by turning off the signal for platelet aggregation, and as a consequence, PTB-1B deficient platelets show reduced clot retraction [48,49].…”
Section: Som Application For Repurposingmentioning
confidence: 72%
“…(7)). This hypothesis is supported by the observation that very low doses of Aspirin can reduce bleeding in portal hypertension patients, which has been explained by COX-2 inhibition [47]. Based on the LeadHopper® prediction, one might speculate that this surprising opposite effect to the standard indication of Aspirin might also be attributed to PTB-1B inhibition: PTP-1B is required for normal platelet thrombus formation by turning off the signal for platelet aggregation, and as a consequence, PTB-1B deficient platelets show reduced clot retraction [48,49].…”
Section: Som Application For Repurposingmentioning
confidence: 72%
“…This increased level, observed in portal hypertensive rats, decreased to a normal value in the group that received the treatment with ASA 15 cH. 20…”
Section: Effect Of Aspirin 15 Ch On Rats With Portal Hypertension Andmentioning
confidence: 79%
“…Inhibition of PGI 2 should not interfere with the gastric protective PGE 2 but cardiovascular complication risk may increase. Recent studies have shown that increased PGI 2 in the rat PVL model corresponds with a decreased in vivo platelet activity resulting in reduced laser-induced thrombus formation (13). Although this protects against cardiovascular accidents it exacerbates variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased risks, the biological basis for the cardiovascular consequences of COX-2 inhibition continues to be elucidated and research into COX-2 inhibitors and COX enzymology persists (13,15,20,35,63). In particular, two recent publications into the gastrointestinal advantages of COX-2 inhibitors shows that the role of COX inhibitors are still relevant and as such the role of COX isoforms in PGI 2 biosynthesis and PHT is significant (17,29).…”
mentioning
confidence: 99%